Disparitas Sosial, Komunikasi Politik dan Partisipasi Politik Gender - Nurul Azizah; Mohammad Armoyu (Maddah : Jurnal Komunikasi dan Konseling Islam, 2024)
The aim of this research is to analyze and offer strategies to increase women's political participation in Islamic societies. The benefit of this research is to increase awareness in Islamic communities about the importance of gender equality in participating in politics and to increase women's political participation in Islamic communities. The theory used in this research is the social construction theory of gender. This research uses descriptive qualitative methods to analyze data related to gender inequality in political participation in Islamic communities. Data was collected through interviews with several informants who are experienced in Islamic politics and society. The research results show that gender inequality in political participation in Islamic communities is visible in several aspects. First, women are still given less opportunities to participate in the political decision-making process. Second, women still experience discrimination in accessing information and resources needed for political participation. Third, women still experience stigma and stereotypes that prevent them from participating in politics. The suggestions and recommendations in this research, such as increasing awareness, developing resources, eliminating stigma and stereotypes, and developing partnerships, are expected to help overcome gender inequality in political participation in Islamic communities.